2017
DOI: 10.3390/min7040060
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Longwall Mining Layout Approach for Extraction of Deep Coal Deposits

Abstract: As more easily mined deposits are depleted, the reserves are becoming more limited and less favorable. Deposits of coal or trona that are being longwall mined are deep and are getting deeper. Coal bursts and bumps frequently occur within development entries in longwall mining of deep mines due to high stresses. This paper presents a novel patented longwall mining layout "Longwall Mining with Split-level Gate roads (LMSG)" that has the potential to mitigate several problems related to deep mining (Patent No. ZL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Based on the results of the performed model testing as well as the analyses and in situ observation for the analyzed case in coal seam, the authors presented the following conclusions: the results of the numerical calculations confirmed that the longwall panel stability depends not just on the powered support capacity, but also on the correct geometrical parameters of the powered support. The relationship between rocks and powered supports was also presented in [14][15][16].…”
Section: Justification For Building a Geometry Monitoring Systemmentioning
confidence: 99%
“…Based on the results of the performed model testing as well as the analyses and in situ observation for the analyzed case in coal seam, the authors presented the following conclusions: the results of the numerical calculations confirmed that the longwall panel stability depends not just on the powered support capacity, but also on the correct geometrical parameters of the powered support. The relationship between rocks and powered supports was also presented in [14][15][16].…”
Section: Justification For Building a Geometry Monitoring Systemmentioning
confidence: 99%
“…The finite-element software was applied to simulate the bolt and anchor cable support. The beam element could not only conveniently define the anchorage lengths of the bolt and anchor cable, the cohesive strength and stiffness of the resin roll, but also could bear the tensile and shear effects of surrounding rocks [31]. Therefore, the beam element was used in the simulation.…”
Section: Calculation Of the Bolt And Anchor Cable Parametersmentioning
confidence: 99%
“…The efficiency of underground mining of coal seams depends on the correct choice of the applied mining technology. The main method of coal mining at present is the development by longwalls [1][2][3], the work of which is to conduct mine workings along the contour of large rectangular blocks of coal (longwall panels). The overlying rocks lose their support during coal extraction, and some of these rocks fall down.…”
Section: Introductionmentioning
confidence: 99%